PREDICTORS OF EARLY POST-OPERATIVE TRANSIENT URINARY INCONTINENCE AFTER HOLMIUM LASER ENUCLEATION OF PROSTATE - TRIPATHI, SOMESH; DIXIT, PRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Despite having various benefits, post-operative transient urine incontinence (TUI) is a significant consequence of holmium laser prostate enucleation (HoLEP) in a small percentage of patients. To manage benign prostatic hypertrophy, it is critical to establish predictive risk factors of early postoperative TUI after HoLEP. Methods: One hundred participants participated in this hospital-based study over the course of 15 months in a tertiary care facility in Mohali and Punjab. All indoor benign prostatic hyperplasia patients who underwent HoLEP treatment from a single surgeon and were monitored for at least 3 months after the procedure made up the study population. Clinical information that was deemed pertinent was recorded. Results: The study’s participants had an average age of 68.54 +/− 7.72 years. Patients who had experienced acute urine retention made up 48% of the population. Mean prostate size and mean International Prostate Symptom Score (IPSS) were 64.19 ml and 28.35 ml, respectively, preoperatively. Diabetes mellitus, prostate volume (>58 cc), overall operation time (>131 min), enucleated prostate volume (42 g), total energy used (>154 kJ), and percentage decrease in prostate-specific antigen (60%) were all substantially linked to post-operative TUI. Total energy was found to be a predictor for post-operative TUI in multivariate analysis. Conclusion: The following factors were discovered to be statistically linked with postoperative TUI: Diabetes mellitus, prostate volume (>58 cc), total operation time (>131 min), enucleated prostate volume (42 g), total energy used (>154 kJ), and reduction in Prostate Specific Antigen (60%) Multivariate research revealed that the only independent predictor for post-operative TUI was total energy consumed.